PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI VARIABEL INTERVENING KEPUASAN PELANGGAN PADA ONLINE TRAVEL AGENT (OTA) AGODA (SURVEI PADA PENGGUNA AGODA) - Supriadi Siagian; Free Antonius Simanjuntak (Journal of Global Business and Management Review, 2023)
Service quality is one way to meet customer needs and desires as well as the accuracy of delivery and realize customer expectations. By achieving customer satisfaction, customer loyalty can be created. The aim of this research is to find out directly whether service quality has a significant effect on customer loyalty through intervening customer satisfaction. The number of samples in this research was 105 samples. The sampling technique in this research was a non-probability sampling technique by determining respondents using purposive sampling with the conditional characteristics being customers who had used Agoda. And distribution of questionnaires is done online using Google Form. Measurements from the questionnaire were carried out using a Likert scale and data analysis techniques to measure the research variables used SPSS 23 software. The results of this research show that service quality has a significant effect on customer satisfaction (1). Service quality has a significant effect on customer loyalty (2). Customer satisfaction has a significant effect on customer loyalty (3). Service quality has a significant effect on customer loyalty through intervening customer satisfaction (4). Therefore, it is necessary to maintain the quality of service to customers so that customers remain loyal and feel satisfied with the products offered